X-ray crystallography - Girolami, Gregory S., 1956- (University Science Books, 2016)
This book is a well-balanced, thorough, and clearly written introduction to the most important and widely practiced technique to determine the arrangement of atoms in molecules and solids. Featuring excellent illustrations and homework problems throughout, the book is intended both for advanced undergraduate and graduate students who are learning the subject for the first time, as well as for those who have practical experience but seek a text summarizing the theory of diffraction and X-ray crystallography. It is organized into three parts: Part 1 deals with symmetry and space groups, Part 2 explains the physics of X rays and diffraction, and Part 3 examines the methods for solving and refining crystal structures. -- Provided by publisher.
Keywords: X-ray crystallography.; Crystallography.; Chemistry, Physical and theoretical.; X-rays -- Diffraction.; Chemistry.; Physical sciences.; elektronické knihy; electronic books